APPLICATION OF FORCE MAJEURE CLAUSES IN AGREEMENTS BUSINESS RENTAL DURING THE COVID-19 PANDEMIC - Andini Barata (LPPM Universitas Tadulako, 2023)
The development of the COVID-19 pandemic has disrupted various aspects of life, one of which is in terms of agreements where there is a breach of contract because one party cannot fulfill its achievements due to the COVID-19 force majeure. The formulation of the problem in this research is how to apply the COVID-19 force majeure clause in leasing contracts during the pandemic and what the settlement policy is for leasing contracts that occur during the COVID-19 pandemic. This research aims to find out how the force majeure clause is applied in leasing agreements during the COVID-19 pandemic and how to resolve it. This research uses an empirical juridical research method, namely a method used to obtain primary data and find the truth based on facts in the field through interviews with related parties. The results of this research explain that the leasing institution PT. FIF Group Astra Palu City and Sinarmas Multifinance Palu City have not implemented a force majeure clause in the contract with the lessee. The two leading institutions have formed various policies to overcome defaults during the COVID-19 pandemic by referring to the Regulation of the Financial Services Authority of the Republic of Indonesia Number 14/POJK.05/2020 concerning Countercyclical Policies on the Impact of the Spread of Coronavirus Disease 2019 for Non-Bank Financial Services Institutions and continue to pay attention to the precautionary principle that does not harm the lessee or the lessor. This research provides suggestions for leasing institutions to include standard clauses regarding COVID-19 force majeure in written contracts with lessees, and for lessees to be more cooperative in responding to policies issued by leasing institutions.